Microbiological Stability of Traditional Rendang Boleces Prepared from Spent Hen Meat Under Ambient Storage Conditions - Rahmi Holinesti; Anni Faridah; Mimi Harni; Noveria Sjafrina; Ranggi Rahimul Insan; Sari Mustika (Green Engineering Society, 2026)
Spent hen meat has potential as an alternative raw material for traditional ready-to-eat meat products; however, its microbiological quality during storage requires evaluation. This study assessed the microbiological quality of rendang boleces (a meatball-like product) prepared from spent hen meat using Total Plate Count (TPC) analysis and Salmonella spp. detection. Samples were stored under ambient conditions (25–28°C) for 0, 2, 4, and 6 days. TPC values increased during storage, from 2.67 log CFU/g on day 0 to 4.63 log CFU/g on day 6. Samples stored for up to two days remained within the maximum permissible limit established by the Indonesian National Standard (SNI). In contrast, higher microbial counts were observed on days 4 and 6, indicating progressive microbial growth during extended storage. Salmonella spp. was not detected in any sample throughout the observation period. These findings indicate that rendang boleces maintained acceptable microbiological quality for up to two days under ambient storage conditions. The study also highlights the importance of appropriate storage and hygienic handling practices to maintain the quality of ready-to-eat meat products derived from spent hen meat while supporting the sustainable utilization of poultry resources in line with SDG 12 (Responsible Consumption and Production).